2006
DOI: 10.1096/fj.06-6133fje
|View full text |Cite
|
Sign up to set email alerts
|

An invertebrate‐like phototransduction cascade mediates light detection in the chicken retinal ganglion cells

Abstract: Prebilaterian animals perceived ambient light through nonvisual rhabdomeric photoreceptors (RPs), which evolved as support of the chordate visual system. In vertebrates, the identity of nonvisual photoreceptors and the phototransduction cascade involved in nonimage forming tasks remain uncertain. We investigated whether chicken retinal ganglion cells (RGCs) could be nonvisual photoreceptors and the nature of the photocascade involved. We found that primary cultures of chicken embryonic RGCs express such RP mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 47 publications
6
75
0
1
Order By: Relevance
“…Conversely, when the light is on, cones and rods become hyperpolarized, stopping the release of glutamate and thus preventing the depolarization and subsequent HC response. In addition to their typical role in the retinal circuits, in nonmammalian vertebrates HCs may conserve vestiges of ancient photoreceptor cells (Scheme 1, scenario 2) as clearly demonstrated for ipRGCs (2,6,17,18). In teleosts, it has been reported that retinal HCs expressing VA opsin or OPN4 can intrinsically respond to light (28,29).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Conversely, when the light is on, cones and rods become hyperpolarized, stopping the release of glutamate and thus preventing the depolarization and subsequent HC response. In addition to their typical role in the retinal circuits, in nonmammalian vertebrates HCs may conserve vestiges of ancient photoreceptor cells (Scheme 1, scenario 2) as clearly demonstrated for ipRGCs (2,6,17,18). In teleosts, it has been reported that retinal HCs expressing VA opsin or OPN4 can intrinsically respond to light (28,29).…”
Section: Discussionmentioning
confidence: 93%
“…In teleosts, it has been reported that retinal HCs expressing VA opsin or OPN4 can intrinsically respond to light (28,29). OPN4 is found in brain, iris, and retinal cells of vertebrates (1,3,5,6,12,(17)(18)(19) and highly conserved through evolution (38). In mammals OPN4 is confined to ipRGCs; however, the distribution of multiple Opn4s (Opn4m and Opn4x) in diverse retinal cell types of nonmammalian vertebrates suggests a biological function of higher complexity (see review in ref.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another indirect line of evidence comes from studies of chick RGCs, a small percentage of which express melanopsin [7]. In relatively pure cultures of embryonic chick ganglion cells, transcripts for G q but not transducin have been identified [8]. In the same cultures, light suppresses the release of melatonin and this effect, which may be mediated by melanopsin, requires PLC.…”
Section: Evidence For a Rhabdomeric Phosphoinositide Cascadementioning
confidence: 99%